Interest Affect and Type of benefits in the Implementation of the Slumless City Program in Bone Regency, South Sulawesi - Herlina Sakawati; Sulmiah Sulmiah; Rudi Salam; Widyawati Widyawati (Program Pascasarjana Universitas Negeri Makassar, 2021)
The handling of slum areas through the City Without Slums program has been implemented in a number of areas since 2016, after the Ministry of Public Works and Public Housing issued Circular No. 40/SE/DC/2016. The program is expected to improve the quality of the environment so that the level of welfare and the regional economy will increase. Through this article, the researcher intends to provide an overview of the implementation of the City Without Slums program in Bone Regency, from the aspect of Interest Affect and Type of Benefits, through a qualitative research method. By using Interactive Model Analysis, in processing the data from the observations. documentation and interviews, it was found that the City Without Slums program in Bone Regency was carried out with an orientation to the public interest with a decentralized system and community empowerment. The government formulates a strategy for dealing with slum areas by paying attention to the suitability between community needs and existing problems, then the community is used as the main actor in implementing the strategy. This program has also provided collective benefits for the local government and the people of Bone Regency, in terms of the economy and the provision of public services. In order for the implementation of the KOTAKU program in Bone Regency to run optimally, the government needs to pay attention to the capabilities and number of existing program implementers.